PENGARUH KOMUNIKASI, PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TONGKUNO SELATAN KABUPATEN MUNA - Sukrin Sukrin; Diamin M (Unib Press Universitas Bengkulu, 2021)
The purposes of this study are: 1) To determine and analyze the effect of communication on employee performance. 2) To find out and analyze the effect of training on employee performance. 3) To determine and analyze the effect of motivation on employee performance. 4) To determine and analyze the effect of communication, training and motivation simultaneously on employee performance. The research design used is quantitative research. The population in this study were all employee extension workers of South Tongkuno District, Muna Regency as many as 47 people, using saturated sampling. Data collection in the form of interviews and questionnaires. The data analysis technique used multiple regression model with the help of SPSS 24 software. The results showed that: 1). communication has a positive and significant effect on performance. 2) training has a positive and significant effect on performance.3. motivation has a positive and significant effect on performance. 4. Communication, training and motivation have a positive and significant effect on performance